HUBUNGAN PERAN ORANGTUA DENGAN TINGKAT STRES SAAT HOSPITALISASI PADA ANAK USIA PRA SEKOLAH DI 6 WEST MURNI TEGUH MEMORIAL HOSPITAL MEDAN - Yudika Rani Hasugiani; Rostime Hermayerni Simanullang (PT. Hasba Edukasi Mandiri, 2025)
Background: Hospitalization is a crisis condition for every child who is hospitalized. Children must adjust to difficult situations while in hospital, for example treatment, health workers, and separation from family, especially parents. The role of parents is very important in supporting the health and well-being of children, both physiological and psychological health, especially in child care, where parents will face lifelong responsibility in self-management of their child's condition. Research objectives: This study aims to examine the relationship between the role of parents and the level of stress during hospitalization in preschool-aged children at 6 West Murni Teguh Memorial Hospital Medan. Method: This type of research is quantitative with a cross sectional survey design. The sampling technique in this research was total sampling, with a sample of 16 respondents, data collection was carried out by looking at the inclusion criteria and exclusion criteria. Data analysis used the Spearman correlation test. Research results: It was found that there was a relationship between the role of parents and the level of stress during hospitalization in preschool children. This is proven by the Spearmen correlation test with a p-value of 0.001 and a correlation coefficient of 0.733 is obtained, so it can be concluded that this indicates a high relationship between the role of parents and stress levels in pre-school children. Conclusion: It can be concluded that there is a relationship between the role of parents and the level of stress during hospitalization in preschool children. Suggestion: For future researchers to increase the number of samples and it is recommended to use cluster techniques in research and add variables such as parenting patterns, in order to get broader results and coverage.